Implementation Curriculum with the Tamyiz Method at Muhammadiyah Boarding School (MBS) Pleret - Muhammad Hatta Minulyo; Muhammad Raja Miftah Hidayatullah; Saefudin; Abdul Hopid; Mario Jufri (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2025)
This research examines the implementation of curriculum with the Tamyiz method at Muhammadiyah Boarding School (MBS) Pleret as an Islam-based educational approach that integrates religious values with academic achievement. The Tamyiz method, which was developed in 2010, offers a practical and fun approach in learning to translate the Qur'an and yellow scriptures through the basic theory of quantum nahwu-shorof. This research uses a qualitative approach with in-depth interviews to explore educational management at MBS Pleret. The results show that the curriculum implemented at MBS Pleret is a combination of the national curriculum and Muhammadiyah pesantren-based curriculum, complemented by Tamyiz learning. The implementation of this method has proven effective in improving the ability of students to understand and translate the Qur'an lafziyah. With a pleasant learning atmosphere and supported by adequate facilities, the Tamyiz method is able to produce a generation that is intellectually intelligent, strong in faith, and virtuous.